Madurez para peso corporal de cinco genotipos de gallinas camperas - Fernández, Ramiro; Librera, José Ernesto; Di Masso, Ricardo José; Canet, Zulma Edith (Universidad Nacional de Rosario, 2024)
Poster y resumen